Інформаційні технології як інструмент розвитку інклюзивного аграрного бізнесу - Степаненко, С. В.; Дяченко, О. П. (My University, 2023)
Доступ до управлінської інформації у рамках сучасних інтернет-сервісів є виключно важливим для агробізнесу та консолідується у межах аграрних інформаційних систем. У статті проведено аналітичний моніторинг сучасних інформаційних продуктів і технологій, які постають найбільш перспективними з позицій підвищення результативності і рівня інклюзивності управління аграрними процесами. З’ясовано, що на практиці дієвими інструментами таких інформаційних систем є технології smart-обробки даних, smart-ферми, digital-інструменти точного землеробства і тваринництва, облаштування smart-теплиць, використання БПЛА, логістичні управлінські рішення, інформаційні системи управління персоналом, спеціалізовані програмні аналітичні продукти тощо. Визначено, що інформаційні системи можуть стати ефективним інструментом досягнення завдань сталого розвитку і цілей Зеленого курсу. Обґрунтовано перспективні можливості використання сучасних інформаційних технологій у інклюзивному аграрному бізнесі. Визначено, що виробничо-технологічні можливості інформаційних технологій мають бути доповнені digital-інструментами у сфері фінансового, інвестиційного, кадрового агроменеджменту, а також можливостями рівного і справедливого доступу аграріїв до логістичних мереж і сталих ланцюгів постачання та реалізації сільськогосподарської продукції. Achieving competitive advantages and solving the most important tasks of sustainable inclu-sive development for modern society is possible only using information technologies. Broad mul-tifunctional digitalization of the economy creates new opportunities and prospects for managing the agricultural sector and solving tasks that are relevant for the rural areas of Ukraine and the world community ensuring food security. Access to management information within modern Internet services is extremely important for agribusiness and is consolidated within agricultural information systems. Analytical monitoring of modern information products and technologies, which appear to be the most promising from the point of view of increasing the effectiveness and level of inclusiveness of management of agrarian processes, is carried out in the article. It has been found that in practice, the effective tools of such information systems are smart data processing technologies, smart farms, digital tools for precision agriculture and animal husbandry, smart greenhouses, the use of UAVs, logistical management solutions, personnel management information systems, specialized software analytical products, etc. It was determined that information systems can become an effective tool for achieving the goals of sustainable development and the goals of the Green Course. Prospective possibilities of using modern information technologies in inclusive agrarian business are substantiated. Along with technical and technological services, the tools of equal and fair access of farmers to information platforms of a financial nature and the creation of information and logistics opportunities for sustainable supply chains and sales of agricultural products are of exceptional importance for the further development of inclusive agrarian business. It was determined that the production and technological capabilities of information technologies should be supplemented with digital tools in the field of financial, investment, personnel agricultural management, as well as opportunities for equal and fair access of farmers to logistics networks and sustainable chains of supply and sale of agricultural products.
Information technologies as a tool for the development of inclusive agricultural business
Keywords: цифровізація; сільське господарство; digital-інструменти; smart-ферми; сталий розвиток; сільські території; агроменеджмент; digitization; agriculture; digital tools; smart farms; sustainable development; rural areas; agrarian management